The physiological functions and therapeutic potential of exosomes during the development and treatment of polycystic ovary syndrome - Zhang, Zhenghong; Shi, Congjian; Wang, Zhengchao (Frontiers in Physiology, 2023)
Polycystic ovary syndrome is a very common disease of gynecological endocrine, accompanied by irregular menstruation, hyperandrogenism, metabolic abnormalities, reproductive disorders and other clinical symptoms, which seriously endangers women's physical and mental health, but its etiology and pathogenesis are not completely clear. Recently, the contribution of exosomes to the diagnosis and treatment of various diseases in the biomedical field has attracted much attention, including PCOS. Exosomes are extracellular vesicles secreted by cells, containing various biologically active molecules such as cell-specific proteins, lipids, and nucleic acids. They are important signaling regulators in vivo and widely participate in various physiopathological processes. They are new targets for disease diagnosis and treatment. Considering the important role of non-coding RNAs during the development and treatment of PCOS, this article takes exosomal miRNAs as the breakthrough point for elucidating the physiological functions and therapeutic potential of exosomes during the development and treatment of PCOS through analyzing the effects of exosomal miRNAs on ovarian follicle development, hormone secretion, oxidative stress, inflammatory response and insulin resistance, thus providing new research directions and theoretical basis for PCOS pathogenesis, clinical diagnosis and prognosis improvement.